Transcriptome-based gene profiling provides novel insights into the characteristics of radish root response to Cr stress with next-generation sequencing - Xie, Yang; Ye, Shan; Wang, Yan; Xu, Liang; Zhu, Xianwen; Yang, Jinlan; Feng, Haiyang; Yu, Rugang; Karanja, Benard; Gong, Yiqin; Liu, Liwang (Frontiers in Plant Science, 2015)
Radish (Raphanus sativus L.) is an important worldwide root vegetable crop with high nutrient values and is adversely affected by non-essential heavy metals including chromium (Cr). Little is known about the molecular mechanism underlying Cr stress response in radish. In this study, RNA-Seq technique was employed to identify differentially expressed genes (DEGs) under Cr stress. Based on de novo transcriptome assembly, there were 30,676 unigenes representing 60,881 transcripts isolated from radish root under Cr stress. Differential gene analysis revealed that 2,985 uingenes were significantly differentially expressed between Cr-free (CK) and Cr-treated (Cr600) libraries, among which 1,424 were up-regulated and 1,561 down-regulated. Gene ontology (GO) analysis revealed that these DEGs were mainly involved in primary metabolic process, response to abiotic stimulus, cellular metabolic process and small molecule metabolic process. Kyoto encyclopedia of genes and genomes (KEGG) enrichment analysis showed that the DEGs were mainly involved in protein processing in endoplasmic reticulum, starch and sucrose metabolism, amino acid metabolism, glutathione metabolism, drug and xenobiotics by cytochrome P450 metabolism. RT-qPCR analysis showed that the expression patterns of 12 randomly selected DEGs were highly accordant with the results from RNA-seq. Furthermore, many candidate genes including signaling protein kinases, transcription factors and metal transporters, chelate compound biosynthesis and antioxidant system, were involved in defense and detoxification mechanisms of Cr stress response regulatory networks. These results would provide novel insight into molecular mechanism underlying plant responsiveness to Cr stress and facilitate further genetic manipulation on Cr uptake and accumulation in radish.